Sustainability of social enterprises – a framework to enable long term impact of their missions - Chong, Sook-Leng (2021)
This research is about sustainability of social enterprises. It is about enabling long-term existence of these ventures to continue creating and delivering environmental, and social impact, solving societal issues with innovative solutions where governments and private sectors have been ineffective or eluded entirely.